High Current Density Electrical Breakdown of TiS3 Nanoribbon‐Based Field‐Effect Transistors. (15th February 2017) - Molina‐Mendoza, Aday J.; Island, Joshua O.; Paz, Wendel S.; Clamagirand, Jose Manuel; Ares, Jose Ramón; Flores, Eduardo; Leardini, Fabrice; Sánchez, Carlos; Agraït, Nicolás; Rubio‐Bollinger, Gabino; van der Zant, Herre S. J.; Ferrer, Isabel J.; et al.
Abstract : The high field transport characteristics of nanostructured transistors based on layered materials are not only important from a device physics perspective but also for possible applications in next generation electronics. With the growing promise of layered materials as replacements to conventional silicon technology, the high current density properties of the layered material titanium trisulfide (TiS3 ) are studied here. The high breakdown current densities of up to 1.7 × 10 6 A cm −2 are observed in TiS3 nanoribbon‐based field‐effect transistors, which are among the highest found in semiconducting nanomaterials. Investigating the mechanisms responsible for current breakdown, a thermogravimetric analysis of bulk TiS3 is performed and the results with density functional theory and kinetic Monte Carlo calculations are compared. In conclusion, the oxidation of TiS3 and subsequent desorption of sulfur atoms play an important role in the electrical breakdown of the material in ambient conditions. The results show that TiS3 is an attractive material for high power applications and lend insight into the thermal and defect activated mechanisms responsible for electrical breakdown in nanostructured devices. Abstract : TiS3 nanoribbons‐based field‐effect transistors are found to stand one of the highest current densities among nanostructured materials. The mechanisms that lead to the nanodevice breakdown are investigated in the bulk material by thermogravimetric analysis measurements and by density functional theory calculations together with kinetic Monte Carlo simulations, and are found to be due to oxygen‐mediated sulfur desorption.